Geology geoheritage & water quality of Jeli Hotspring as a potential geotourism site in Jeli District, Kelantan - Zurfarahin Zulkarnain (2015)
A research study had been carried out at Jell Hotspring area in the effort to collect and document geological information for its values, characteristics, uniqueness and importance since the area had been left abandon. The distribution of rocks found in study area through petrographic analysis is composed of of monzogranite, granodiorite, microgranite and ryhodacite. The various geological structural found are fracture, formation of pothole, spheroidal weatherig and grus formation. Apart from that, documentation of mankind feature: road and village also conducted. Analysis of water quality for geotourism purposed are being done. The water in the area required treament before being used because the water posses higher content of chemical that are dangerous for mankind.